2018
DOI: 10.3892/or.2018.6843
|View full text |Cite
|
Sign up to set email alerts
|

Histone methyltransferase SUV39H2 serves oncogenic roles in osteosarcoma

Abstract: Suppressor of variegation 3-9 homologue 2 (SUV39H2), a SET domain-containing histone methyltransferase, trimethylates histone H3 at lysine 9 and serves crucial roles in heterochromatin organization and genome stability. SUV39H2 is overexpressed in various types of human cancer, whereas it is almost undetectable in normal adult tissues, except testis. The aim of this study was to investigate a potential role of SUV39H2 in osteosarcoma. In the present study, increased SUV39H2 expression levels were observed in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…Consistent with our research findings, the expression of SUV39H2 is significantly upregulated in OS, whereas depletion of SUV39H2 expression by specific small interfering RNA could dramatically suppress the growth of OS cells, leading to a significant decrease in cell survival rate [9]. In our subsequent experiments, we found that SUV39H2 promotes EMT and migration of OS cells.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with our research findings, the expression of SUV39H2 is significantly upregulated in OS, whereas depletion of SUV39H2 expression by specific small interfering RNA could dramatically suppress the growth of OS cells, leading to a significant decrease in cell survival rate [9]. In our subsequent experiments, we found that SUV39H2 promotes EMT and migration of OS cells.…”
Section: Discussionsupporting
confidence: 90%
“…Histone methyltransferases such as SETD2 are significantly implicated in OS [7]. Moreover, histone methyltransferase SUV39H2 reportedly can promote the occurrence and progression of OS [9]. Therefore, we aimed in this study to investigate the mechanism whereby SUV39H2 affects OS by meditation of the LSD1/CDH1 axis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Suv39h2 is a histone‐lysine N‐methyltransferase, which is involved primarily in the tri‐methylation of Lysine9 on Histone H3, leading to transcriptional repression (O'Carroll et al, ). While overexpression of Suv39h2 is observed in various cancer types (including colorectal cancer, osteosarcoma, and leukemia) and it is thought to promote tumorigenesis (Carvalho Alves‐Silva et al, ; Piao et al, ; Shuai et al, ), it has no documented role in melanoma, and the expression in melanoma is very low (Rambow et al, ). Importantly, the read‐depth analysis showed that the Suv39h2 gene was present at normal levels (i.e., 2n) in the Tyr::CreER T2‐Lar mice.…”
Section: Discussionmentioning
confidence: 99%